2023
DOI: 10.1029/2022ea002794
|View full text |Cite
|
Sign up to set email alerts
|

Moho Inversion by Gravity Anomalies in the South China Sea: Updates and Improved Iteration of the Parker‐Oldenburg Algorithm

Weibo Rao,
Nan Yu,
Gang Chen
et al.

Abstract: The Moho is the interface between crust and mantle, and accurate location of the Moho is important for both resource exploration and deep earth condition and structural change investigations. The theory of the traditional Parker‐Oldenburg (P‐O) method is quite simple and it is widely applied in the frequency domain of Moho depth inversion. However, Moho fluctuation simulations using the P‐O method are not reliable because of the lack of field geographic data constraints during the inversion process and the exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Joint seismic and gravity data, Huang et al (2023) used the Parker-Oldenburg method to invert the Moho topography of the SCS, and found that there is a significant asymmetry in the crustal thickness of the mid-ocean ridges in the Eastern sub-basin. Rao et al (2023) proposed an improved Parker-Oldenburg method that inverted Moho topography in the SCS under the constraints of available geological data. Notably, the Parker-Oldenburg method is extremely dependent on two hyperparameters, the Moho density contrast and the average Moho depth.…”
Section: Introductionmentioning
confidence: 99%
“…Joint seismic and gravity data, Huang et al (2023) used the Parker-Oldenburg method to invert the Moho topography of the SCS, and found that there is a significant asymmetry in the crustal thickness of the mid-ocean ridges in the Eastern sub-basin. Rao et al (2023) proposed an improved Parker-Oldenburg method that inverted Moho topography in the SCS under the constraints of available geological data. Notably, the Parker-Oldenburg method is extremely dependent on two hyperparameters, the Moho density contrast and the average Moho depth.…”
Section: Introductionmentioning
confidence: 99%